A new technique for the diagnosis of fallopian tube patency by using hysteroscopy with ultrasound compared with hysterosalpingography in infertile women - YILDIZHAN, BEGÜM (SPRINGER HEIDELBERG, 2009)
To evaluate the effectiveness of hysteroscopy as a method for the diagnosis of tubal patency using saline distention media. In this prospective study, 62 women between 21 and 38 years with a history of at least 1 year of infertility who underwent hysteroscopy and hysterosalpingography (HSG) on two consecutive cycles were studied. Transvaginal ultrasonography carried out before and after hysteroscopy in order to measure the abdominal fluid (in ml) in the peritoneal cavity of the cul-de-sac. The difference between the two results was calculated. A next cycle HSG was performed and patients were divided into three groups according to whether there was no tubal occlusion (group 1), a unilateral occlusion (group 2) or a bilateral occlusion (group 3): Peritoneal fluid measurements were compared among the three groups. Finally, pain and discomfort were recorded at the end of the process. According to the HSG, 34 women were in group 1, 13 in group 2 and 9 in group 3. Peritoneal fluid measurements were 6.88 +/- A 2.7 ml in group 1, 4.21 +/- A 0.9 ml in group 2 and 1.08 +/- A 0.7 ml in group 3. Statistical differences were found between groups 1 and 3 and between groups 2 and 3 (P < 0.05). All of the patients reported significantly less pain during hysteroscopy in response to HSG. Using saline distension media during hysteroscopic evaluation was effective to allow measurement of the accumulating fluid in the peritoneal cavity and to confirm at least one patent tube with minimal pain.
Keywords: Hysterosalpingography; Hysteroscopy; Tubal patency; Ultrasound; CONTRAST SONOGRAPHY HYCOSY; UTERINE CAVITY